Daring to care : American nursing and second-wave feminism - Malka, Susan Gelfand (Book collections on Project MUSE., 2007)
Arguing that feminism helped to end nursing's subordination to medicine and provided nurses with greater autonomy and professional status, the author examines the impact of second-wave feminism on the nursing field since the 1960s.